Kajian Tumbuhan Obat dari Suku Moraceae Pada Koleksi Kebun Raya Bogor - Sahromi (The Ethnobiological Society of Indonesia, 2021)
The main function of the Botanical Gardens is to conserve plants for ex-situ preservation in the form of living collections. One of the plant families in the Bogor Botanical Gardens is the Moraceae. The Garden has collected species of Moraceae from some regions of Indonesia. The Moraceae family is widely known as the Mulberry (mulberry family) or the Ara (fig family), in Indonesia it is known as the beringin family. Moraceae species have a promising medicinal uses or potentially as herbal medicine, and some have been used as traditional medicine by the local community. The purpose of this study was to carry out an inventory and identification of Moraceae species, collected in the Bogor Botanical Garden, as traditional medicine or potentially as herbal. The result showed that 10 species of Moraceae have been used by the local communities as traditional medicine. The species consisted of Artocarpus elasticus, A. altilis, Ficus adenosperm, F. ampelas, F. fistulosa, F. religiosa, F. variegata, Milicia excelsa, Morus alba, and Streblus asper. Artocarpus altilis has been widely used traditionally, and has undergone research on its efficacy tests, passed preclinical tests, and this species had the potential to be developed into synthetic drugs. Plant species from the Ficus genera which was widely used as a natural medicine was F. religiosa. The species is a well-known traditional medicinal plant, and widely used in India. All parts of this plant were useful as traditional medicine to treating many diseases. The use of Ficus religiosa as a traditional medicine has been well documented and scientific study has been carried out on its phytochemical and pharmacological aspects.